Analysis of the moral judgment of superintendents in Kansas and Nebraska and association with key demographics - Applegate, Joel D. (Kansas State University, 2017)
Public educational leaders are being scrutinized because of scandals that range from embezzlement, cheating on high stake exams for future bonuses, to viewing pornography on school technology. The need for ethical leadership by the superintendent along with moral judgment on decision-making is reflected in the foundation of public educational organizations. The purpose of this quantitative research study is to explore the stage of moral judgment among public school superintendents when faced with moral dilemmas. Also, this research explores whether there is an association between certain demographic variables (enrollment, gender, salary, age, ethical training, total years experience as an administrator, years as a superintendent, highest degree, and place or work,) and moral judgment of the superintendent. The primary question guiding this study is: In the states of Kansas and Nebraska, what is the stage of moral judgment of superintendents when making decisions pertaining to moral dilemmas? The population chosen for this study is the public school superintendents in Kansas and Nebraska. The superintendents completed an online Defining Issues Test 2 (DIT2) questionnaire to assess their cognitive moral development score called the N2 index. The DIT2 is based upon Lawrence Kohlberg’s stages of moral development. The secondary objective is to examine the relationship between moral judgment and demographic variables. The data were analyzed using ANOVA, t test, Mann Whitney U, Kruskal Wallis, and stepwise regression. The researcher sent the online DIT2 instrument electronically to all 514 superintendents. Of the 514 superintendents, 129 completed enough of the survey. Out of the 129, four participants did not provide any demographic data, which brought the total to 125 participants. The superintendents mean N2 index score was 32.28. This put them at the same level of upper high school and first and second year undergraduate students (Bebeau & Thoma, 2003). Using ANOVA to analyze the data from this study indicates that enrollment size and gender significantly influenced superintendents’ stage of moral judgment. Stepwise regression analysis was then indicated that salary was also significantly associated with moral judgment of superintendents. The other variables - years of experience as an administrator, age, ethical training, years as superintendent, highest educational degree and place of work - provided no statistically significant influence on the moral judgment of superintendents. From this study’s findings, recommendations are offered to strengthen educational leadership and moral judgment of school superintendents.
Keywords: moral judgment; superintendents